Procrastination Seen from Parents' Social Support and Self Efficacy of Students - Yustintia Arofa Nurahmawati; Alif Muarifah; Purwadi Purwadi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
Procrastination is carried out by students on the background of several things, such as difficulty making decisions so that students tend to follow decisions even though it is detrimental to themselves. In addition, there are also some students who feel worried and afraid of being wrong in completing assignments but are embarrassed to ask teachers and parents this results in an increase in the level of procrastination at MAN Magelang Regency seen when students are given assignments that are not completed, so they tend to see the results of friends' work. This study aims to empirically examine the relationship between parental social support and self-efficacy with procrastination in MAN students in Magelang Regency. This study uses quantitative methods. The number of subjects in this study amounted to 304 students, the sampling technique used was proportional stratified random. Collecting data using procrastination scale, parental social support scale, and self-efficacy scale. Analysis of the data used in this study using multiple linear regression analysis with assumption test. The results of testing the hypothesis together obtained an R value of 0.811 with a significance value of 0.000 (p <0.01), providing an effective contribution of 65.8%. These results indicate that the hypothesis is accepted that there is a significant relationship between parental social support and self-efficacy with procrastination. This means that the higher the parent's social support and self-efficacy, the higher the level of procrastination. Prokrastinasi dilakukan siswa dilatar belakangi beberapa hal seperti kesulitan mengambil keputusan sehingga siswa cenderung mengikuti keputusan teman meskipun hal tersebut merugikan dirinya sendiri. Selain itu juga terdapat beberapa siswa merasa khawatir dan takut salah dalam menyelesaikan tugas akan tetapi malu bertanya kepada guru maupun orangtua hal tersebut berakibat tingginya tingkat prokrastinasi di MAN Kabupaten Magelang terlihat pada saat siswa diberikan tugas tidak kunjung diselesaikan, sehingga siswa cenderung untuk melihat hasil pekerjaan teman. Penelitian ini bertujuan untuk menguji secara empirik hubungan antara dukungan sosial orangtua dan self efficacy dengan prokrastinasi pada siswa MAN di Kabupaten Magelang. Penelitian ini menggunakan metode kuantitatif. Jumlah subjek dalam penelitian ini berjumlah 304 siswa, teknik pengambilan sampel yang digunakan adalah proportionate stratified random. Pengumpulan data menggunakan skala prokrastinasi, skala dukungan sosial orangtua, dan skala self efficacy. Analisis data yang digunakan dalam penelitian ini menggunakan analisis regresi linier berganda dengan uji asumsi. Hasil uji hipotesis bersama-sama diperoleh nilai R sebesar sebesar 0,811 dengann nilai signifikansi 0,000 (p < 0,01), memberikan sumbangan efektif sebesar 65,8%. Hasil tersebut menunjukkan bahwa hipotesi diterima, yaitu terdapat hubungan yang signifikan antara dukungan sosial orangtua dan self efficacy dengan prokrastinasi. Artinya semakin tinggi dukungan sosial orangtua dan self efficacy mampu untuk menurunkan tingkat prokrastinasi.